Association of HSD11B1 polymorphic variants and adipose tissue gene expression with metabolic syndrome, obesity and type 2 diabetes mellitus: a systematic review - do Nascimento, Filipe Valvassori (Diabetol Metab Syndr, 2015)
The HSD11B1 gene is highly expressed in abdominal adipose tissue, and the enzyme it encodes catalyzes the interconversion of inactive cortisone to hormonally active cortisol. Genetic abnormalities of HSD11B1 have been associated with the development of abnormal glucose metabolism and body fat distribution. To systematically review studies evaluating the association of HSD11B1 gene expression in abdominal adipose tissue and HSD11B1 polymorphisms with obesity, the metabolic syndrome (MetS), and type 2 diabetes (T2DM), we conducted a search in MEDLINE, SCOPUS, and Cochrane Library databases in April 2015. The inclusion criteria were observational studies (cross-sectional, cohort, or case–control), conducted in adults, which analyzed the relationship of HSD11B1 polymorphisms and/or HSD11B1 expression in abdominal adipose tissue with obesity, MetS, or T2DM. Of 802 studies retrieved, 32 met the inclusion criteria (23 gene expression and 9 polymorphism studies). Twenty one studies analyzed the relationship between abdominal subcutaneous and/or visceral HSD11B1 expression with central and/or generalized obesity. Most studies reported that abdominal adipose HSD11B1 expression increased with increasing body mass index (15 studies) and abnormalities of glucose metabolism (7 studies), and varied with the presence of MetS (3 studies). Nine studies analyzed the association of 26 different HSD11B1 polymorphic variants with obesity, MetS, and T2DM. Only an Indian study found an association between a polymorphic variant at the HSD11B1 gene with MetS whereas in Pima Indians another polymorphic variant was found to be associated with T2DM. While the literature suggests that HSD11B1 is hyperexpressed in abdominal adipose tissue in subjects with obesity and abnormal glucose metabolism, this seems to be not true for HSD11B1 gene expression and MetS. Although an association of polymorphic variants of HSD11B1 with MetS in Indians and in the T2DM population of Pima Indians were found, most studies did not find a relationship between genetic polymorphic variants of HSD11B1 and obesity, MetS, and T2DM. Their reported conflicting and inconclusive results, suggesting that polymorphic variants of HSD11B1 may have only a small role in the development of metabolic abnormalities of susceptible populations in the development of MetS and T2DM.